2015
DOI: 10.1002/ece3.1785
|View full text |Cite
|
Sign up to set email alerts
|

Thermal tolerance and climate warming sensitivity in tropical snails

Abstract: Tropical ectotherms are predicted to be especially vulnerable to climate change because their thermal tolerance limits generally lie close to current maximum air temperatures. This prediction derives primarily from studies on insects and lizards and remains untested for other taxa with contrasting ecologies. We studied the HCT (heat coma temperatures) and ULT (upper lethal temperatures) of 40 species of tropical eulittoral snails (Littorinidae and Neritidae) inhabiting exposed rocky shores and shaded mangrove … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 93 publications
(227 reference statements)
1
55
0
3
Order By: Relevance
“…Foot muscle CT max was defined as the temperature at which the organism loses its neuromuscular ability to grasp a vertical surface. Fallen limpets are more susceptible to predation or being washed away by waves, which have negative fitness consequences (Marshall et al 2015); thus, this is an ecologically important metric. Other studies on mollusks and limpets have referred to the temperature of neuromuscular failure or detachment from substratum as the onset of heat coma temperature (HCT) or non-lethal thermal tolerance (Clarke et al 2000, Sokolova & Pörtner 2003, Denny et al 2006, Miller et al 2015, Chapperon et al 2016.…”
Section: Foot Muscle Ct Maxmentioning
confidence: 99%
“…Foot muscle CT max was defined as the temperature at which the organism loses its neuromuscular ability to grasp a vertical surface. Fallen limpets are more susceptible to predation or being washed away by waves, which have negative fitness consequences (Marshall et al 2015); thus, this is an ecologically important metric. Other studies on mollusks and limpets have referred to the temperature of neuromuscular failure or detachment from substratum as the onset of heat coma temperature (HCT) or non-lethal thermal tolerance (Clarke et al 2000, Sokolova & Pörtner 2003, Denny et al 2006, Miller et al 2015, Chapperon et al 2016.…”
Section: Foot Muscle Ct Maxmentioning
confidence: 99%
“…Many intertidal organisms encounter intensive thermal stresses, especially species with limited abilities to regulate body temperature behaviorally (Harley, 2011;Walters et al, 2012;Seabra et al, 2016). Previous studies have shown that many intertidal organisms currently live close to their upper thermal limits and thus are likely to be significantly challenged by future increases in temperature (Stillman, 2002;Somero, 2012;Dong et al, 2015;Marshall et al, 2015). Thus, the rocky intertidal zone is an ideal model system for investigating the relationships between conditions of thermal exposure and adaptation, as well as for elucidating the susceptibility of organisms to the impact of climate change (Mislan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In general, phylogenetic signal of thermal tolerance, particularly upper thermal tolerance, is high for ectothermic species (reviewed in Hoffmann, Chown, & Clusella-Trullas, 2013). For example, Drosophila exhibit quite high phylogenetic signal in upper thermal tolerance (Kellermann et al, 2012), as do snails (Marshall, Rezende, Baharuddin, Choi, & Helmuth, 2015) and lizards (Clusella-Trullas, Blackburn, & Chown, 2011;Grigg & Buckley, 2013). Intertidal crabs also show high phylogenetic signal in upper thermal tolerance, but low signal in lower thermal tolerance (Faria et al, 2017).…”
mentioning
confidence: 99%